2000
DOI: 10.1139/t00-052
|View full text |Cite
|
Sign up to set email alerts
|

Strength behaviour of lime-treated soils in the presence of sulphate

Abstract: Lime has been used extensively to improve the shear strength of fine-grained soils. It has been recently reported that the presence of sulphate causes abnormal volume changes in lime-stabilized soil. The paper presents the strength behaviour of lime-treated montmorillonitic natural black cotton soil in the presence of varying sulphate contents after curing for periods of up to 365 days. Alteration of soil-lime reactions in the presence of sulphate affects the strength development by cementation. Consequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…However, several attempts have been made to address the effect of sulfate/gypsum on the engineering behaviour of soil treated with other additives such as lime, fly ash, ground-granulated blast furnace and so on. Sivapullaiah et al (2000) studied the strength behaviour of lime-treated montmorillonitic natural black cotton soil in the presence of varying sulfate contents after curing for periods of up to 365 d and reported that decrease in strength occurs after longer periods of curing. Ahmed and Ugai (2011) attributed the rapid deterioration in compressive strength for stabilised soil-gypsum under freeze-thaw action mainly to the change in the calcium sulfate hemihydrate to calcium sulfate hydrate by which the cementation property of recycled gypsum is lost.…”
Section: Introductionmentioning
confidence: 99%
“…However, several attempts have been made to address the effect of sulfate/gypsum on the engineering behaviour of soil treated with other additives such as lime, fly ash, ground-granulated blast furnace and so on. Sivapullaiah et al (2000) studied the strength behaviour of lime-treated montmorillonitic natural black cotton soil in the presence of varying sulfate contents after curing for periods of up to 365 d and reported that decrease in strength occurs after longer periods of curing. Ahmed and Ugai (2011) attributed the rapid deterioration in compressive strength for stabilised soil-gypsum under freeze-thaw action mainly to the change in the calcium sulfate hemihydrate to calcium sulfate hydrate by which the cementation property of recycled gypsum is lost.…”
Section: Introductionmentioning
confidence: 99%
“…These soils can be used as construction material (Bell, 1996). Although lime stabilizes the soil rapidly after the treatment, the mechanical properties and strength of soil change over a long period of time (Bell, 1996;Sivapullaiah et al, 2000). Kavak and Akyarlı (2007) present the influence of lime treatment on mechanical properties of clays with laboratory and in-situ tests.…”
Section: Introductionmentioning
confidence: 99%
“…For a similar class soil, Kinuthia et al [13] reported that the LL decreases from 73% to 71, 69 and 67% respectively with 1, 2 and 3% CaSO 4 .2H 2 O for 6%L addition. On the other hand, for the same class soil, Sivapullaiah et al [15] observed that the LL increases from 68% up to 70, 73 and 76% respectively with 0.5, 1 and 3% CaSO 4 for 6%L addition due to the chemical interaction between soil, L and CaSO 4 . However, for the RS stabilized with 8%L on curing for 1 day, the LL decreases from 54.9% to 54.2, 53.7 and 52% respectively with 2, 4 and 6% CaSO 4 .2H 2 O (Table 7).…”
Section: Variation Of Liquid Limit In the Presence Of Caso 4 2h 2 Omentioning
confidence: 95%
“…Furthermore, the magnitude of damage caused by the ettringite depends on the soil nature, the type and the content of additives [3] and the concentration and the type of cation associated with the sulphate anion [13]. Indeed, the effects caused by the presence of different types of sulphates on the geotechnical properties of soils stabilized with additives have been investigated by several researchers [13][14][15][16][17][18][19]. 1 …”
Section: Introductionmentioning
confidence: 99%